From notes to needles: Assessing logbook-based monitoring of child immunization by posyandu cadres in Borong Loe Hamlet - Sadarang, Rimawati Aulia Insani; Mutmainna, Mutmainna; Ihwan, Nur (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Immunization remains a vital intervention for reducing child morbidity and mortality, yet coverage in several rural areas, including Borong Loe Hamlet, remains suboptimal. Previous studies have largely overlooked the role of local health volunteers, such as Posyandu cadres, in strengthening immunization data systems through simple, context-based tools. This study evaluates the effectiveness of using a structured logbook by Posyandu cadres to monitor child immunization activities. The intervention involved distributing a logbook containing 13 structured work plans, followed by a six-month implementation period. Evaluation was conducted using three key indicators: completeness, consistency, and timeliness of recording. Findings revealed an average score of 5.17 out of 10, categorized as “fair,” with consistency scoring highest (5.6) and timeliness lowest (4.6). These results suggest that the logbook facilitates systematic documentation by cadres but highlights the need for continuous training and the provision of visual guidelines to enhance recording accuracy. The logbook model offers a scalable and context-sensitive approach to improving immunization monitoring in resource-limited rural settings. Implications point to the potential of empowering local health actors through targeted tools and support systems to strengthen public health data quality and surveillance mechanisms.